2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009387
|View full text |Cite
|
Sign up to set email alerts
|

“Wink to grasp” — comparing eye, voice & EMG gesture control of grasp with soft-robotic gloves

Abstract: The ability of robotic rehabilitation devices to support paralysed end-users is ultimately limited by the degree to which human-machine-interaction is designed to be effective and efficient in translating user intention into robotic action. Specifically, we evaluate the novel possibility of binocular eye-tracking technology to detect voluntary winks from involuntary blink commands, to establish winks as a novel low-latency control signal to trigger robotic action. By wearing binocular eye-tracking glasses we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…We previously showed that the end-point of visual attention (where one looks) can control the spatial end-point of a robotic actuator with centimetre-level precision (Tostado et al, 2016;Maimon-Mor et al, 2017;Shafti et al, 2019b). This direct control modality is more effective from a user perspective than voice or neuromuscular signals as a natural control interface (Noronha et al, 2017). We showed that such direct augmentation can be used to control a supernumerary robotic arm to draw or paint, freeing up natural two arms to do other activities such as eating and drinking at the same time (Dziemian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the end-point of visual attention (where one looks) can control the spatial end-point of a robotic actuator with centimetre-level precision (Tostado et al, 2016;Maimon-Mor et al, 2017;Shafti et al, 2019b). This direct control modality is more effective from a user perspective than voice or neuromuscular signals as a natural control interface (Noronha et al, 2017). We showed that such direct augmentation can be used to control a supernumerary robotic arm to draw or paint, freeing up natural two arms to do other activities such as eating and drinking at the same time (Dziemian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we demonstrated that our FastOrient algorithm works out-out-of-the-box which does not require a complex training learning pipeline and is sufficient to allow a natural wrist and grasp interaction. With the technology that we have demonstrated, we should be able to use gaze-based 3D positioning of the arm for grasping, as demonstrated in [4]- [6], wink-based detection of grasping intention [7], and now automatic processing of the grasp orientation based on the findings of this paper, without the requirement for the user to fine-tune the orientation of the hand, resulting in a full, intuitive assistive system. We have demonstrated FastOrient across 5 different realistic surfaces and for 26 different objects pertaining to standard activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-modal systems relying on unaffected abilities, e.g. the use of gaze-based robotic end-point control for reaching assistance [4]- [6], or the use wearable robotics controlled through eye winks and voice [7]. In all these cases, a suitable eventual grasp is only possible with the correct orientation of the hand; be it the human hand using an orthotic ( Figure 1-left), or a tele-operated robotic hand, performing the grasp (Figure 1-right).…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that results from healthy subjects are not transferable to the stroke population. In the study of Noronha et al [87], muscle activity was outperformed by wink and voice when assessing the error rate of grasping in healthy subjects. In the present study, we did not observe a statistical significant difference in success rate of the three modalities, but individual false positive rates were higher in wink controlled grasping when compared to the other modalities.…”
Section: Discussionmentioning
confidence: 98%
“…Muscle activity -In order to control the glove using myoelectric signals, a commercial [87]. The procedure used to control the glove by winking has previously been described by…”
Section: Systemmentioning
confidence: 99%